PWE-010 Biofeedback-A simple and Effective way of Managing Rectal Evacuatory Dysfunction Secondary to Pelvic Floor Dyssynergia and Rectal Hyposensitivity. (4th June 2013) - Rimmer, C; Stackhouse, K; Cruickshank, N; Gill, K
Abstract : Introduction: Biofeedback is safe and effective in the management of rectal evacuatory dysfunction (RED), but there is limited data on medium to long-term follow-up. This study evaluated the effectiveness of biofeedback in the medium-term for patients with RED secondary to pelvic floor dyssynergia (PFD) and rectal hyposensitivity (RH). Methods: Prospective data was collected from 2010 –2013 of 81 consecutive patients who underwent specialist nurse-led verbal biofeedback therapy in the form of rectal sensory re-training or balloon expulsion for PFD or RH. The primary outcome measure was patient satisfaction with their symptom improvement, assessed using a visual analogue scale (Likert scale 0–10). Secondary outcome measures were complete spontaneous bowel movements (CSBMs)/week, time to defecation-assessed using bowel diaries, and KESS/SF-36 quality of life questionnaire scores. All discharged patients received telephone follow-up. Results: 85% patients met the primary outcome measure, with the Likert score improving [mean baseline 3.2 (1–7) vs. post-biofeedback 7.6 (5–9) p < 0.001]. Improvements were seen in CSBMs/week [mean baseline: 3.0 (1–14) vs. post-biofeedback: 6.9 (1–13) P < 0.001] and time taken to defecate in minutes [mean baseline: 18.7 (5–60) vs. post-biofeedback: 8.7(5–30) P < 0.001]. Significant improvements were seen in KESS [mean baseline 13.1 (9–18) vs. post-biofeedback 4.9 (0–16) p < 0.001] and SF-36 scores. Mean number of biofeedback treatments received was four (1–6). 89% of patients discharged still meet the primary endpoint at a mean follow-up of 19 months (range 7–36). Conclusion: Biofeedback has a key role to play in the management of rectal evacuatory dysfunction secondary to pelvic floor dyssynergia and rectal hyposensitivity, with the improvement being maintained in the medium-term. Disclosure of Interest: None Declared.